Highly Efficient and Stable Solar Cells with Hybrid of Nanostructures and Bulk Heterojunction Organic Semiconductors. Issue 6 (9th April 2019) - Ram, Kiran Sreedhar; Singh, Jai
Abstract: The power conversion efficiency (PCE) of a hybrid bulk hetero‐junction organic solar cell with an active layer of a blend of PBDT TS1 (donor) and PCBM (acceptor) incorporated with copper zinc tin sulfide (CZTS) quantum dots (QDs) and zinc oxide (ZnO) nanowires is simulated. It is found that the incorporation of CZTS‐QDs of a single radius (1.5 nm) enhances the PCE from 9.1% to 12.34% and of 13 different radii CZTS‐QDs elevates PCE to 14.96%. This enhancement occurs mainly due to the enhancement in absorption that enhances short‐circuit current density ( J sc ) and fill factor (FF). Finally, a layer of ZnO nanowires is added on top of the glass to reduce the reflection losses and absorption of ultraviolet light in the active layer that causes degradation and reduces the stability of organic solar cells (OSCs). The hybrid structure, thus simulated, has an enhanced PCE of 16.32% and is expected to be relatively more stable. It is expected that the results of this simulation may inspire all researchers interested in the fabrication of highly efficient hybrid OSCs. Abstract : The incorporation of CZTS‐QDs of 13 different sizes and ZnO‐NWs on top of glass layer enhances the absorption and stability of a hybrid bulk‐hetero junction organic solar cell with the structure ZnO‐NWS/Glass/ITO/PEDOT:PSS/CZTS‐QDs:PBDT‐TS1:PCBM/Al and results in a PCE of 16.32%.